A formalist analysis in how Lewis Carroll portrays Alice character in "Alice's Adventures in Wonderland" - Asgar Widhasworo Rochmansyah Putra; Alifian Kusuma Bahtiar; Wahyu Indah Mala Rohmana (Lililacs Journal, 2024)
The article presents a formalist analysis of Alice's characterization in the novel "Alice's Adventures in Wonderland" from the point of view of the author of the fictional work Lewis Caroll. This research article explores how Alice's actions, dialogues, and interactions contribute to her characterization, emphasizing the traits of curiosity, open-mindedness, empathy, and assertiveness. It also investigates the role of each episode in shaping Alice's journey and highlights the importance of dreams, growth, and her encounter with the Caterpillar. The article concludes by emphasizing the formalist perspective and references various dissertations, conference proceedings, and books related to the analysis of Alice's character in the novel.